Analisis Kinerja Anggota Unit Reskrim dalam Penyelesaian Kasus Dipolsek Majalaya Resort Karawang - Sujana; Rismayadi, Budi; Pertiwi, Wike (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Human resources are an achievement or advantage for an agency, with good human resources, the agency's achievement is good and benefits. This research uses qualitative research with descriptive methods. In this study the results obtained by researchers show that the performance of the majalaya police crime unit is less than optimal in achieving the targets of various cases that occur in the majalaya police jurisdiction, which is caused by the quantity and quality of the members of the crime unit itself.